Allosteric Probe Recognition Initiated Cascade Transcription Amplification for Sensitive Analysis of Exosomes. (30th March 2022) - Lei, Huabin; Ma, Yaru; Zhang, Hui; Cao, Zenghui; Zhang, Heng
Abstract: Sensitive and accurate analysis of exosomes is important for many biological processes including as a biomarker for cerebral venous thrombosis (CVT) diagnosis and therapy. Herein, we established a sensitive and specific exosome detection approach based on target recognition initiated cascade signal amplification. In this method, an allosteric probe was designed with a hairpin structure for specific recognition of the exosome followed by signal amplification. After the cascade signal amplification process, spinach RNA sequences bind to DFHBI (( Z )‐4‐(3, 5‐difluoro‐4‐hydroxybenzylidene)‐1, 2‐dimethyl‐1 H ‐imidazol‐5(4 H )‐one) to produce enhanced fluorescence signal (approximate 2000 fold than that of inactive DFHBI). Compared with former proposed exosome detection techniques, this method exhibited a comparable detection range, but with an easy‐to‐design toolbox. Therefore, we believe that the proposed approach holds great potential for exosome based early diagnosis and prognosis of disease. Abstract : A sensitive and specific exosome detection approach is established based on target recognition initiated cascade signal amplification. There are in total three procedures in the approach including: i) allosteric probe based specific recognition of target exosomes, ii) polymerase based chain extension and Nt ⋅ BstNBI based chain liberation, and iii) generated spinach RNA sequences binding to DFHBI to produce enhanced fluorescence signal.